Agile Management in Online Learning Platforms: Strategies for Dealing with Uncertainty in the Digital Age - Nicolas Kevin Sulistyawardhana; Enik Rahayu; Henry Yuliamir (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
Abstract. This study examines the application of Agile Management principles in online learning platforms, focusing on the challenges and benefits experienced during implementation. Through qualitative research, including interviews and case studies, the research explores how platforms have adopted Agile practices, such as iterative cycles, regular feedback, and flexibility, to enhance responsiveness and adaptability. The findings reveal that the majority of platforms have integrated Agile principles, with a significant focus on overcoming challenges like resistance to change and a lack of training. Participants reported improved collaboration, increased efficiency, and the ability to respond to changes effectively. However, challenges remain, including the need for hybrid models combining Agile with traditional management frameworks. This study contributes valuable insights into the effectiveness of Agile practices in educational technology and offers directions for future research on enhancing Agile implementation in diverse educational settings.